2016
DOI: 10.1080/13548506.2016.1263755
|View full text |Cite
|
Sign up to set email alerts
|

Health consequences of intimate partner violence against married women: a population-based study in northern Iran

Abstract: The effects of different types of intimate partner violence (IPV) on mental health are understudied. The aim of this study was to analyse the association between women's mental health and physical, psychological and sexual IPV. We invited subjects of a population-based survey conducted in 2015 in Rasht, Iran, on IPV against women to complete the General Health Questionnaire (GHQ-28). The present research study is a secondary study based on these data and archival data from the 2015 study. For analysis, multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
1
14
0
2
Order By: Relevance
“…We found that among forms of IPV, experiencing severe combined victimization had the strongest effect on subsequent substance use in females and harassment was not a robust predictor of males' substance use disorder. This finding supports other research's findings (e.g., 159,315,323,324,326) that different types of IPV have different consequences. However, caution must be applied when interpreting these results, as forms of abuse co-occur and it is difficult to distinguish their tangled effects (329).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that among forms of IPV, experiencing severe combined victimization had the strongest effect on subsequent substance use in females and harassment was not a robust predictor of males' substance use disorder. This finding supports other research's findings (e.g., 159,315,323,324,326) that different types of IPV have different consequences. However, caution must be applied when interpreting these results, as forms of abuse co-occur and it is difficult to distinguish their tangled effects (329).…”
Section: Discussionsupporting
confidence: 91%
“…while characteristics of a sample (e.g., clinical or selective versus representative samples) may affect the magnitude of association between IPV and alcohol use/abuse (131), some previous longitudinal studies have not included population-based samples.Fourth: although some studies -mostly cross-sectional-have suggested different consequences of different types and patterns of IPV(159,315,(323)(324)(325)(326), our knowledge about the differential effects of forms of IPV on victims' substance abuse is limited.…”
mentioning
confidence: 99%
“…Individuals with mental disorders also present the aggravation of having impaired social relationships ( 33 ) . Thus, common psychiatric disorders in victims of intimate partner violence may include somatic symptoms, anxiety, insomnia, social dysfunction and depression ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Another study with 2,091 women showed that when it comes to the pattern of intimate partner violence, psychological aggression is more frequent than physical aggression, sexual coercion or injury ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation